Pengaruh Audit Laporan Keuangan, Penerapan Good Governance, Dan Peran Internal Audit Terhadap Kualitas Laporan Keuangan - Ahmad Mukoffi; Yayuk Sulistiyowati; Roswita Ina Reda; As’adi As’adi (-, 2023)
The notes to the financial statements contain the financial statements and additional information. Our understanding of financial statements grows with the amount of information contained in financial statement disclosures. The purpose of this study was to determine the effect of internal audit, good governance, and audit of financial statements on the quality of financial reports. For the primary data of this research, internal audit respondents from manufacturing companies in Malang City were surveyed. The data used in this study were analyzed using multiple linear regression. According to research findings, internal audit, sound corporate governance, and financial report audit significantly affect the accuracy of financial reports. They lend credence to the notion that internal and financial report audits have a major impact on the caliber of financial reports. On the other hand, the quality of financial reporting does not appear to be much influenced by a strong corporate governance component